Anatomical distribution and clinical significance of middle cerebral artery M2 segment vessel occlusions and its cortical branches in acute ischaemic stroke patients - Philipp Gruber; Jatta Berberat; Javier Anon; Luca Remonda; Lukas Andereggen; Paola Valbuena; Renske Sassenburg (BMJ Neurology Open)
Background Characterisation of anatomical distribution and the clinical impact of middle cerebral artery M2 (MCA-M2) segment occlusion and its subsequent cortical branches (CBs) in acute ischaemic stroke patients (AIS).Methods Retrospective, monocentric study analysing radiological and clinical data of AIS patients with MCA-M2 segment occlusion with regard to the anatomic distribution of MCA-M2 occlusion and its subsequent CB.Results A total of 203 patients (median age 77 (IQR 66–83) years, 112 women) were included. There was an equal distribution of right-sided versus left-sided MCA-M2 vessel occlusions (right: n=97; left: n=106), as well as with a median number of affected MCA-M2 CBs of 4 (IQR, 3–6) and a median National Institute of Health Stroke Scale score (NIHSS) on admission of 9 (3–15). For both hemispheres, CBs of the inferior trunks were significantly more affected than the superior trunks. Endovascular treatment (EVT, n=94) was associated with a significant better outcome compared with patients with medical management alone (p=0.027).Conclusion In acute MCA-M2 segment occlusions, inferior trunks are significantly more affected compared with the superior trunks. The subsequent CBs of the paracentral region of both hemispheres are more commonly involved. In eloquent vascular territories, EVT was more often performed.